탄자니아 농촌지역 내 소규모 바이오가스 시설 재가동 효과 평가: 실내 대기질 개선 및 소화액 비료로써의 활용 가능성 - 김민상; Min-sang Kim; 조홍목; Hongmok Jo; 박영미; Yeongmi Park; 한의정; Uijeong Han; 권재훈; Jae Hoon Gwon; 이태환; Taehwan Lee; et al. (유기물자원화, 2025)
청정에너지에 대한 접근은 여전히 많은 개발도상국에서 중요한 과제로 남아 있으며, 탄자니아를 포함한 아프리카에서는 여전히 목재 등의 바이오매스를 주요 가정용 연료로 사용하고 있다. 탄자니아는 2014년 농촌전역에 약 12,000개의 바이오가스 플랜트를 설치하였으나, 현재 대부분은 시설 운전이 중지된 상태이며, 이와 더불어 현재 다양한 보건 및 자원 관련 문제에 직면해 있다. 따라서 본 연구는 탄자니아에 설치된 기존 소규모 바이오가스 시설의 재가동이 가져올 보건 및 농업적 이점을 평가하기 위해, 아루샤(Arusha) 지역 Jiro 마을을 대상으로 실내 대기질 평가 및 소화 슬러지의 농업용 비료 사용 가능성을 비교 분석하였다. 실내 대기질 평가는 바이오매스 또는 바이오가스를 사용하는 가정의 PM₁₀ 농도를 비교하여 진행되었으며, 바이오매스를 사용하는 가정 내 PM₁₀ 농도는 평균 16,452 μg/m³로 WHO 권고 기준보다 약 365배 높은 수준으로 나타났다. 반면, 바이오가스를 사용하는 가정에서는 PM₁₀가 미검출되었다. 또한, 소화 슬러지의 농업용 비료로서의 사용 가능성 평가는 상추를 대상으로 소화액 기반 비료를 활용한 작물 생장 실험을 수행하였으며, 소화액과 화학비료의 단독 조건 및 다양한 비율로 혼합한 혼합비 등 총 6가지 처리 조건에서 식물 생장 성능을 평가하였다. 그 결과, 소화 슬러지는 화학비료보다 잎 생장이 더 우수했으며, 혼합 조건에서는 소화액과 화학비료를 9:1로 혼합한 조건에서 가장 균형 잡힌 생장 효과가 나타났다. 이는 소규모 바이오가스 시설의 운영은 실내 대기오염과 관련된 건강위험을 줄이는 동시에 농촌지역 내 농가를 위한 화학비료의 대체 자원으로써 활용될 수 있음을 보여준다. 따라서, 소규모 바이오가스 시설의 재가동은 탄자니아 농촌지역의 공중보건, 에너지 활용성 및 농업생산성 향상에 있어 가장 효율적인 해결책으로 적용할 수 있을 것으로 판단된다. Access to clean energy remains a critical challenge in many developing countries, and in Africa, including Tanzania, biomass such as firewood continues to serve as the primary household fuel. In 2014, Tanzania installed approximately 12,000 biogas plants across rural areas. However, most of these facilities are currently non-operational, and the country continues to face significant health and resource-related challenges. This study was conducted in the Jiro site of the Arusha region to evaluate the health and agricultural benefits of reactivating small-scale biogas plants. Indoor air quality was assessed by comparing PM₁₀ concentrations in households using biomass or biogas. The results showed that PM₁₀ concentrations in biomass-using households averaged 16,452 μg/m³, approximately 365 times higher than the WHO recommended limit, while no PM₁₀ emissions were detected in biogas utilizing households. In addition, a plant growth experiment was conducted to evaluate the potential use of digestate as an agricultural fertilizer with lettuce. Plant growth performance was assessed under six treatment conditions including digestate, chemical fertilizer, and mixtures of the two at varying ratios. The results showed that digestate treatment resulted in superior leaf growth compared to chemical fertilizer, with the 9:1 digestate to chemical fertilizer mixture producing the most balanced growth within mixture results. These findings demonstrate that the application of small scale biogas plants can reduce indoor air pollution and associated health risks, while also serving as an effective alternative fertilizer source for rural farmers. Therefore, the reactivation of small scale biogas plants represents a practical and efficient solution to improve public health, energy access, and agricultural productivity in rural Tanzania.